Air Pollutant Mapping with a Mobile Laboratory during the BEE-TEX Field Study - Tara I. Yacovitch; Scott C. Herndon; Joseph R. Roscioli; Cody Floerchinger; W. Berk Knighton; Charles E. Kolb (SAGE Publishing, 2015)
The Aerodyne Mobile Laboratory was deployed to the Houston Ship Channel and surrounding areas during the Benzene and Other Toxics Exposure field study in February 2015. We evaluated atmospheric concentrations of volatile organic hydrocarbons and other hazardous air pollutants of importance to human health, including benzene, 1,3-butadiene, toluene, xylenes, ethylbenzenes, styrene, and NO 2 . Ambient concentration measurements were focused on the neighborhoods of Manchester, Harrisburg, and Galena Park. The most likely measured concentration of 1,3-butadiene in the Manchester neighborhood (0.17 ppb) exceeds the Environmental Protection Agency's E-5 lifetime cancer risk level of 0.14 ppb. In all the three neighborhoods, the measured benzene concentration falls below or within the E-5 lifetime cancer risk levels of 0.4-1.4 ppb for benzene. Pollution maps as a function of wind direction show the impact of nearby sources.